2001
DOI: 10.1038/90831
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of protein interactions in plant cells

Abstract: The protein NPR1/NIM1 is required for the induction of systemic acquired resistance (SAR) in plants and has been shown to interact with members of the TGA/OBF family of basic leucine zipper (bZIP) transcription factors. However, to date, there is no method available to monitor such interactions in plant cells. We report here an in vivo protein fragment complementation assay (PCA), based on association of reconstituted murine dihydrofolate reductase (mDHFR) with a fluorescent probe to detect protein-protein int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 24 publications
2
72
1
2
Order By: Relevance
“…This finding was consistent with the results of a recent study using a transient expression system in tobacco and tomato protoplasts (Subramaniam et al, 2001). The mechanism by which SA enhances NPR1-TGA2 complex formation is unknown.…”
Section: Discussionsupporting
confidence: 82%
“…This finding was consistent with the results of a recent study using a transient expression system in tobacco and tomato protoplasts (Subramaniam et al, 2001). The mechanism by which SA enhances NPR1-TGA2 complex formation is unknown.…”
Section: Discussionsupporting
confidence: 82%
“…NPR1 is localized in both the cytoplasm and the nucleus of unstimulated cells, but concentrates in the nucleus in response to SA and, in fact, nuclear localization of NPR1 is required for PR gene expression (Kinkema et al, 2000). Furthermore, using an in vivo protein fragment complementation assay, based on association of reconstituted murine dihydrofolate reductase (mDHFR) with a fluorescent probe to detect protein-protein interactions, it has been shown that the interaction between NPR1 and the bZIP factor TGA2 is itself induced by SA and localized predominantly in the nucleus (Subramaniam et al, 2001). Thus, the interaction of transcription factor(s) with NPR1 provides a link between an SAR-inducing agent, SA, and the changes in gene expression that are associated with SAR.…”
mentioning
confidence: 99%
“…Further, such analysis is not limited to a specific cell type; we have already demonstrated the utility of PCA strategies in bacteria and mammalian cells and more recently in plant cells (Pelletier et al, 1998;Michnick, 1999, 2001;Subramaniam et al, 2001). We have demonstrated that pharmacological perturbations of interactions can be observed, even if the site of action of the perturbant is distant from the interaction being studied.…”
Section: Summary and Perspectivesmentioning
confidence: 97%